Nanoscale ultrafast dynamics in Bi2Te3 thin film by terahertz scanning near-field nanoscopy - Ziyu Huang; Jing Li; Peiyan Li; Lin Du; Mingcong Dai; Jiahua Cai; Zejun Ren; Tianxiao Nie; Xiaojun Wu (iScience)
Summary: Ultrafast laser interactions with topological insulators (TIs) have garnered tremendous interest for understanding light-matter interactions and developing optoelectronic devices across visible to terahertz (THz) regions owning to their high carrier mobility and sensitivity to electric fields. In particular, within the THz regime, TIs hold considerable promise to realize advanced emitters, modulators, and detectors because of their fascinating ultrafast THz dynamics. However, a detailed understanding of TIs’ THz dynamics necessitates access to both nanoscale and femtosecond timescale. By utilizing THz scattering-type scanning near-field optical microscopy, we investigated THz time-domain spectroscopy, optical-pump THz probe, and THz emission in TI thin films at nanoscale. We analyzed their static scattering characteristics, morphology, and observed THz emission and photocarrier dynamics lasting approximately 10 ps, with dependencies of thickness and power. Our findings reveal the nanoscale ultrafast dynamics of TIs and demonstrate THz s-SNOM’s potential to enhance compact THz device development.